Spatial memory performances of aged rats in the water maze predict levels of hippocampal neurogenesis - Drapeau, Elodie (National Academy of Sciences, 2003)
Neurogenesis occurs within the adult dentate gyrus of the hippocampal formation and it has been proposed that the newly born neurons, recruited into the preexistent neuronal circuits, might be involved in hippocampal-dependent learning processes. Age-dependent spatial memory impairments have been related to an alteration in hippocampal plasticity. The aim of the current study was to examine whether cognitive functions in aged rats are quantitatively correlated with hippocampal neurogenesis. To this end, we took advantage of the existence of spontaneous individual differences observed in aged subjects in a hippocampal-dependent task, the water maze. We expected that the spatial memory capabilities of aged rats would be related to the levels of hippocampal neurogenesis. Old rats were trained in the water maze, and, 3 weeks after training, rats were injected with 5-bromo-2′-deoxyuridine (BrdUrd, 50 or 150 mg/kg) to label dividing cells. Cell proliferation was examined one day after the last BrdUrd injection, whereas cell survival and differentiation were determined 3 weeks later. It is shown that a quantitative relationship exists between learning and the number of newly generated neurons. Animals with preserved spatial memory, i.e., the aged-unimpaired rats, exhibited a higher level of cell proliferation and a higher number of new neurons in comparison with rats with spatial memory impairments, i.e., the aged-impaired rats. In conclusion, the extent of memory dysfunction in aged rats is quantitatively related to the hippocampal neurogenesis. These data reinforce the assumption that neurogenesis is involved in memory processes and aged-related cognitive alterations.